Relationship and marriage in the Andes - Ossio, Juan M. (1981)
It is possible that in our environment, accustomed to thinking that anthropology is an exotic science, which at most is concerned with studying the survivals of the past or aspects that are not significant at the present time, it is considered that the book that we are going to presenting is further proof of the digressive tendencies of this discipline. Many, then, will ask themselves what is the relevance of a book that bears the title Kinship and marriage in the Andes*; And not a few will wonder what relevance the Andean has at a time when Peruvian society is spoken of in terms of social classes, miscegenation, a homogeneous nationality, industrial development; that is, at a time when only the urban is enhanced and the Andean man is disdained, even denying him the right to maintain his own symbols and customs.